ADMISSIONS DUE TO ACUTE MYOCARDIAL INFARCTION AND DAY OF THE WEEK - Khattak, M. Tahir; Kazmi, S. Nasir Hussain Shah (Journal of Ayub Medical College Abbottabad, 1991)
ABSTRACT A retrospective analysis was carried out of patients admitted to Cardiac Care Unit (CCU) of Civil Teaching Hospital, Abbottabad over a one-year period with an acute myocardial infarction. The number of admissions due to acute myocardial infarction on each day of the week was looked at, both in males and females of all age groups. There was a significant difference from the uniform distribution with peak admissions on Saturdays and a minimum number of admissions on Fridays.